The Impact of Programmed Death-Ligand 1 Expression on the Prognosis of Early Stage Resected Non-Small Cell Lung Cancer: A Meta-Analysis of Literatures - Shi, Tao; Zhu, Shuai; Guo, Hengjuan; Li, Xiongfei; Zhao, Shikang; Wang, Yanye; Lei, Xi; Huang, Dingzhi; Peng, Ling; Li, Ziming; Xu, Song (Frontiers in Oncology, 2021)
Introduction Previous studies have demonstrated that programmed cell death-ligand 1 (PD-L1) serves as biomarker for poor prognosis and survival in advanced-stage non-small cell lung cancer (NSCLC) patients. However, the merit of PD-L1 expression to predict the prognosis of early stage NSCLC patients who underwent complete resection remains controversial. In the present study, we performed a meta-analysis to investigate the relationship between PD-L1 expression and prognosis in patients with early stage resected NSCLC. Methods Electronic databases, including PubMed, EMBASE, and the Cochrane Library, were searched until July 23 2020 for studies evaluating the expression of PD-L1 and the prognosis of resected NSCLCs. Hazard ratios (HRs) with 95% confidence intervals (CIs) of overall survival (OS) and disease-free survival (DFS) were pooled and analyzed. Heterogeneity and publication bias analyses were also assessed. Results A total of 15 studies involving 3,790 patients were considered in the present meta-analysis. The pooled HR indicated that PD-L1 expression related to a much shorter DFS (HR = 1.56, 95% CI: 1.18–2.05, p < 0.01), as well a significantly worse OS (HR = 1.68, 95% CI: 1.29–2.18, p < 0.01). Furthermore, our analysis indicated that PD-L1 expression was significantly associated with gender (male vs. female: OR = 1.27, 95% CI:1.01–1.59, p = 0.038), histology (ADC vs. SCC: OR = 0.54, 95% CI:0.38–0.77, p = 0.001), TNM stage (I vs. II–III: OR = 0.45, 95% CI:0.34–0.60, p = 0.000), smoking status (Yes vs No: OR = 1.43, 95% CI:1.14–1.80, p = 0.002) and lymph node metastasis (N+ vs N−: OR = 1.97, 95% CI:1.26–3.08, p = 0.003). Conclusions The results of this meta-analysis suggest that PD-L1 expression predicts an unfavorable prognosis in early stage resected NSCLCs. The role of personalized anti-PD-L1/PD-1 immunotherapy in the adjuvant settings of resected NSCLC warrants further investigation.